Reducing Glucokinase Activity to Enhance Insulin Secretion: A Counterintuitive Theory to Preserve Cellular Function and Glucose Homeostasis - Whitticar, Nicholas B.; Nunemaker, Craig S. (Frontiers in Endocrinology, 2020)
Pancreatic beta-cells are the only cells in the body that can synthesize and secrete insulin. Through the process of glucose-stimulated insulin secretion, beta-cells release insulin into circulation, stimulating GLUT4-dependent glucose uptake into peripheral tissue. Insulin is normally secreted in pulses which allows for robust signaling at the liver. Long before type 2 diabetes is diagnosed, beta-cells become oversensitive to glucose, causing impaired pulsatility and overstimulation in fasting levels of glucose. The resulting hypersecretion of insulin can cause poor insulin signaling and clearance at the liver, leading to hyperinsulinemia and insulin resistance. Continued overactivity can eventually lead to beta-cell exhaustion and failure at which point type 2 diabetes begins. To prevent or reverse the negative effects of overstimulation, beta-cell activity can be reduced. Clinical studies have revealed the potential of beta-cell rest to reverse new cases of diabetes, but treatments lack durable benefits. In this perspective, we propose an intervention that reduces overactive glucokinase activity in the beta-cell. Glucokinase is known as the glucose sensor of the beta-cell due to its high control over insulin secretion. Therefore, glucokinase overactivity may be responsible for hyperinsulinemia early in the disease and can be inhibited to restore normal stimulus-secretion coupling. We have previously reported that reducing glucokinase activity in prediabetic mouse islets can correct glucose sensing and restore pulsatility. Building on this finding, we review the importance of pulsatile insulin secretion in the liver and beta-cell and highlight how restoring pulsatility by targeting early pathological changes in the beta cell may improve glucose homeostasis.